2021
DOI: 10.1063/5.0063475
|View full text |Cite
|
Sign up to set email alerts
|

Fluid dynamics of respiratory droplets in the context of COVID-19: Airborne and surfaceborne transmissions

Abstract: The World Health Organization has declared COVID-19 a global pandemic. Several countries have experienced repeated periods of major spreading over the last two years. Many people have lost their lives, employment, and the socioeconomic situation has been severely impacted. Thus, it is considered to be one of the major health and economic disasters in modern history. Over the last two years, several researchers have contributed significantly to the study of droplet formation, transmission, and lifetime in the c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
33
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 65 publications
(34 citation statements)
references
References 82 publications
1
33
0
Order By: Relevance
“…Combining the results from the four cases, it is shown that: when the boat's forward door is open, a significant airflow forms in the boat, which carries the viruses to make extensive contacts with the passengers in the back seat rows; when the forward door is closed, the viruses mainly sink due to gravity and the diffusion is limited to a small area. These two behaviours are also observed by relevant experimental and computational COVID-19 studies for other environments, as summarised in the review of Katre et al (2021) . More ship speed conditions (V = 12 and 18 knots) have also been tested for the open-door scenario, concerning an infected passenger speaking.…”
Section: External Airflow Entering the Vesselsupporting
confidence: 53%
“…Combining the results from the four cases, it is shown that: when the boat's forward door is open, a significant airflow forms in the boat, which carries the viruses to make extensive contacts with the passengers in the back seat rows; when the forward door is closed, the viruses mainly sink due to gravity and the diffusion is limited to a small area. These two behaviours are also observed by relevant experimental and computational COVID-19 studies for other environments, as summarised in the review of Katre et al (2021) . More ship speed conditions (V = 12 and 18 knots) have also been tested for the open-door scenario, concerning an infected passenger speaking.…”
Section: External Airflow Entering the Vesselsupporting
confidence: 53%
“…It is now recognized that the respiratory particles, exhaled by an infected individual, are ranging from smaller than up to larger than in diameter; see Vuorinen et al 45 and references therein, e.g., Refs. 2 , 22 , 25 , and 26 . The largest follow ballistic trajectories landing quickly on nearby surfaces whereas the smaller droplets undergo evaporation within seconds and act as infective aerosol particles in air.…”
Section: Introductionmentioning
confidence: 99%
“…Second, as introduced previously, LES and DNS are the most advanced methods for cough/sneeze flow simulations. These methods can improve the accuracy of turbulent cough/sneeze puff prediction in indoor environments [ 27 , 28 , [31] , [32] , [33] , [34] ]. However, the significantly refined grid and time-dependent algorithm in turbulence resolution make it too expensive in terms of computational cost, especially for many practical applications such as complex scenarios with multiple infectious sources in a room and external conditions.…”
Section: Introductionmentioning
confidence: 99%